Analisis rantai pasok dan rantai nilai komoditas cabai Provinsi Jambi menuju perdagangan antar pulau dan eskpor - Muhammad Ridwansyah; Rayandra Ashar; Fuad Muchlis; Muhammad Donal Mon; Sopyan Aldino; Mauwlana Syukron (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2022)
Jambi Province has great potential in pursuing horticultural production such as chili, not only to meet people's needs, but also opportunities for inter-regional trade and export. This study aims to 1) to get an overview of the supply chain and value chain of horticultural product commodities in Jambi Province; 2) To determine the position of Jambi Province horticultural product commodities for inter-regional trade purposes (Jambi and Batam); 3) To formulate a trading strategy for horticultural commodities for Jambi and Riau Islands (Batam Island). This study uses a qualitative descriptive method and uses a SWOT analysis. The results showed that the horticultural value chain is divided into 2 activities, namely the main activity consisting of incoming logistiks (horticultural raw material input), operations (horticultural production process into semi-finished materials), logistiks (output), and horticultural marketing. Second, supporting activities consisting of horticultural production infrastructure, HR development, technology development, and marketing and sales. The right strategy to use is a progressive strategy, meaning that the internal conditions of the chili commodity in Jambi Province are at a developing and progressing stage.